Mother-to-infant vertical transmission in early life: a systematic review and proportional meta-analysis of Bifidobacterium strain transmissibility - Eduard Flores Ventura; María Esteban-Torres; Miguel Gueimonde; Douwe van Sinderen; Omry Koren; Lindsay J. Hall; Nicola Segata; Mireia Valles-Colomer; Maria Carmen Collado (npj Biofilms and Microbiomes)
Abstract Early-life colonization is a critical developmental process influencing infant biological programming, with bifidobacteria playing a key role. This systematic review examines the transmissibility of Bifidobacterium strains from mothers to infants. Adhering to Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines, 31 articles from 2009 to 2024 were selected from 2825 screened titles and abstracts. Using a narrative synthesis and meta-analysis, the review focuses on studies employing strain-level metagenomic approaches (Protocol registry CRD: CRD42023490507). Ten studies using shotgun metagenomic sequencing identified specific strains of B. adolescentis, B. angulatum, B. bifidum, B. breve, B. pseudocatenulatum, B. catenulatum, and B. longum shared between mothers and infants. A meta-analysis of 810 mother–infant pairs revealed an overall species transmissibility estimate of 30% (95% CI: 0.17; 0.44), with B. longum strains persisting in infants’ guts for up to 6 months. Strain transmissibility was higher in vaginally delivered infants compared to those delivered by caesarean section. This review highlights the high transmission rates of maternal Bifidobacterium strains in early-life gut seeding, particularly B. bifidum and B. longum. Despite ongoing research, uncertainties remain regarding the precise characteristics, transmission routes, and mechanisms of transmitted strains. Comprehensive approaches, including metagenomic sequencing and longitudinal studies, are needed to understand the role of vertical transmission in infant gut microbiome engraftment and its functional implications.